Lire Ricœur depuis la périphérie - Wolff, Ernst (Philosophie politique, 2021)
At the basis of Paul Ricœur's philosophy, there is an intense and practical engagement with the urgent issues of his time - (de)colonization, globalization, modernity, cultural plurality, geopolitics. Examining this neglected fact reinvigorates the contemporary relevance of his thought and revitalizes social-political hermeneutics.